Digital Transformation in Higher Education: A Case Study on Strategic Plans - Ö. H. Kuzu (Высшее образование в России)
Digital transformation is considered as an inevitable process for higher education systems like all socio-economic institutions and systems. The digital transformation, which paradoxically incorporates both challenges and conveniences, has to become the focus of corporations’ strategies. The aim of this study is to determine the status of digital transformation in universities’ strategies. For this purpose, the strategic plans of 18 Turkish universities, which ranked at the top 1000 most often in the world rankings, were evaluated with the content analysis method. Findings indicate that expressions about the components of digital transformation in the strategic plans of the universities were gathered under 4 themes, 14 categories and 35 codes. The expressions of the universities about digital transformation are coded under the category of diversity and flexibility of learning technologies, especially education theme and distance/open learning. It is observed that universities have the least digital transformation strategies concerning research and social service missions. In this sense, it was concluded that universities could not perform digital transformation beyond technological infrastructure renewal into an integrated transformation model and strategic vision. The results of the study were compared with empirical and theoretical studies in the literature. For universities and future studies, it was proposed that Turkish universities are compareable with the universities abroad, which show the successful examples of the digital transformation, and that the quantitative and/or qualitative methods related to the subject can be applied by internal and external stakeholders, especially in the sector’s evaluations.